Time-Dependent Changes in Protein Composition of Medial Prefrontal Cortex in Rats with Neuropathic Pain - Ujcikova, Hana; Robles, Dagoberto; Yue, Xu; Svoboda, Petr; Lee, Yeon Sun; Navratilova, Edita (International journal of molecular sciences, 2022)
Chronic pain is associated with time-dependent structural and functional reorganization of the prefrontal cortex that may reflect adaptive pain compensatory and/or maladaptive pain-promoting mechanisms. However, the molecular underpinnings of these changes and whether there are time-dependent relationships to pain progression are not well characterized. In this study, we analyzed protein composition in the medial prefrontal cortex (mPFC) of rats at two timepoints after spinal nerve ligation (SNL) using two-dimensional gel electrophoresis (2D-ELFO) and liquid chromatography with tandem mass spectrometry (LC-MS/MS). SNL, but not sham-operated, rats developed persistent tactile allodynia and thermal hyperalgesia, confirming the presence of experimental neuropathic pain. Two weeks after SNL (early timepoint), we identified 11 proteins involved in signal transduction, protein transport, cell homeostasis, metabolism, and apoptosis, as well as heat-shock proteins and chaperones that were upregulated by more than 1.5-fold compared to the sham-operated rats. Interestingly, there were only four significantly altered proteins identified at 8 weeks after SNL (late timepoint). These findings demonstrate extensive time-dependent modifications of protein expression in the rat mPFC under a chronic neuropathic pain state that might underlie the evolution of chronic pain characterized by early pain-compensatory and later aberrant mechanisms.
Keywords: Hyperalgesia; Rats; prefrontální mozková kůra; proteomika; potkani Sprague-Dawley; míšní nervy; Time Factors; Gene Expression Regulation; neuralgie; mužské pohlaví; Prefrontal Cortex; krysa rodu Rattus; Pain Measurement; měření bolesti; regulace genové exprese; Proteomics; zvířata; Spinal Nerves; Tandem Mass Spectrometry; chromatografie kapalinová; Neuralgia; časové faktory; hyperalgezie; Rats, Sprague-Dawley; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Male; Animals